Does hormonal therapy improve sperm retrieval rates in men with non-obstructive azoospermia: a systematic review and meta-analysis. (8th May 2022) - Tharakan, Tharu; Corona, Giovanni; Foran, Daniel; Salonia, Andrea; Sofikitis, Nikolaos; Giwercman, Aleksander; Krausz, Csilla; Yap, Tet; Jayasena, Channa N; Minhas, Suks
Abstract: BACKGROUND: The beneficial effects of hormonal therapy in stimulating spermatogenesis in patients with non-obstructive azoospermia (NOA) and either normal gonadotrophins or hypergonadotropic hypogonadism prior to surgical sperm retrieval (SSR) is controversial. Although the European Association of Urology guidelines state that hormone stimulation is not recommended in routine clinical practice, a significant number of patients undergo empiric therapy prior to SSR. The success rate for SSR from microdissection testicular sperm extraction is only 40–60%, thus hormonal therapy could prove to be an effective adjunctive therapy to increase SSR rates. OBJECTIVE AND RATIONALE: The primary aim of this systematic review and meta-analysis was to compare the SSR rates in men with NOA (excluding those with hypogonadotropic hypogonadism) receiving hormone therapy compared to placebo or no treatment. The secondary objective was to compare the effects of hormonal therapy in normogonadotropic and hypergonadotropic NOA men. SEARCH METHODS: A literature search was performed using the Medline, Embase, Web of Science and Clinicaltrials.gov databases from 01 January 1946 to 17 September 2020. We included all studies where hormone status was confirmed. We excluded non-English language and animal studies. Heterogeneity was calculated using I 2 statistics and risk of bias was assessed using Cochrane tools. We performed a meta-analysis on all the eligible controlled trials to determine whether hormone stimulation (irrespective of class) improved SSR rates and also whether this was affected by baseline hormone status (hypergonadotropic versus normogonadotropic NOA men). Sensitivity analyses were performed when indicated. OUTCOMES: A total of 3846 studies were screened and 22 studies were included with 1706 participants. A higher SSR rate in subjects pre-treated with hormonal therapy was observed (odds ratio (OR) 1.96, 95% CI: 1.08–3.56, P  = 0.03) and this trend persisted when excluding a study containing only men with Klinefelter syndrome (OR 1.90, 95% CI: 1.03–3.51, P  = 0.04). However, the subgroup analysis of baseline hormone status demonstrated a significant improvement only in normogonadotropic men (OR 2.13, 95% CI: 1.10–4.14, P  = 0.02) and not in hypergonadotropic patients (OR 1.73, 95% CI: 0.44–6.77, P  = 0.43). The literature was at moderate or severe risk of bias. WIDER IMPLICATIONS: This meta-analysis demonstrates that hormone therapy is not associated with improved SSR rates in hypergonadotropic hypogonadism. While hormone therapy improved SSR rates in eugonadal men with NOA, the quality of evidence was low with a moderate to high risk of bias. Therefore, hormone therapy should not be routinely used in men with NOA prior to SSR and large scale, prospective randomized controlled trials are needed to validate the meta-analysis findings.